2006
DOI: 10.1136/jnnp.2005.082651
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal atrophy but not memory deficit predicts progression to dementia in patients with mild cognitive impairment

Abstract: Background: The diagnosis of mild cognitive impairment (MCI) is clinically unhelpful, as many patients with MCI develop dementia but many do not. Objective: To identify clinical instruments easily applicable in the clinical routine that might be useful to predict progression to dementia in patients with MCI assessed in the outpatient facility of a memory clinic. Participants and methods: 52 dementia-free patients (mean (standard deviation) age 70 (6) years; 56% women) with MCI, and 65 healthy controls (age 69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 18 publications
(16 reference statements)
5
61
0
Order By: Relevance
“…Anyway, this is in agreement with several studies regarding the manual segmentation of hippocampus, which have reported that baseline hippocampal volume is an indicator of future progression to AD [21,[70][71][72][73]. This is also in agreement with studies based on visual rating, which clearly found MTL atrophy in patients who subsequently converted to AD [74][75][76].…”
Section: Yushkevich Et Alsupporting
confidence: 81%
“…Anyway, this is in agreement with several studies regarding the manual segmentation of hippocampus, which have reported that baseline hippocampal volume is an indicator of future progression to AD [21,[70][71][72][73]. This is also in agreement with studies based on visual rating, which clearly found MTL atrophy in patients who subsequently converted to AD [74][75][76].…”
Section: Yushkevich Et Alsupporting
confidence: 81%
“…A prospective MRI study showed that total cerebral, ventricular, and hippocampal atrophy was important for the prognosis in AD (21). Geroldi et al reported that medial temporal lobe atrophy detected by volumetric MRI was predictive for progression of dementia in MCI patients (22). Bell-McGinty et al reported that MCI patients had loss of volume of the bilateral middle temporal gyrus and hippocampus compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Our inclusion and exclusion criteria for MCI were based on previous seminal studies (Albert et al, 1991;Devanand et al, 1997;Flicker et al, 1991;Petersen et al, 1995Petersen et al, , 1997Petersen et al, , 2001Portet et al, 2006;Geroldi et al, 2006). Study inclusion criteria were all of the following: (i) complaint by the patient, or report by a relative or the general practitioner, of memory or other cognitive disturbances; (ii) Mini-Mental State Examination (MMSE; Folstein et al, 1975) score of 24 to 27/30, or MMSE of 28 and higher plus low performance (score of 2/6 or higher) on the clock drawing test (Shulman, 2000); (iii) sparing of instrumental and basic activities of daily living, or functional impairment stably due to causes other than cognitive impairment, such as physical impairments, sensory loss, gait or balance disturbances, etc.…”
Section: Diagnostic Criteriamentioning
confidence: 99%